SACRAMENT AS A CULTURAL TRAIT IN RAJVAMSHI COMMUNITY OF NEPAL - Khatiwada, Som Prasad (Researcher: A Research Journal of Culture and Society, 2018)
Rajvamshi is a local ethnic cultural group of eastern low land Nepal. Their traditional villages are scattered mainly in Morang and Jhapa districts. However, they reside in different provinces of West Bengal India also. They are said Rajvamshis as the children of royal family. Their ancestors used to rule in this region centering Kuchvihar of West Bengal in medieval period. They follow Hinduism. Therefore, their sacraments are related with Hindu social organization. They perform different kinds of sacraments. However, they practice more in three cycle of the life. They are naming, marriage and death ceremony. Naming sacrament is done at the sixth day of a child birth. In the same way marriage is another sacrament, which is done after the age of 14. Child marriage, widow marriage and remarriage are also accepted in the society. They perform death ceremony after the death of a person. This ceremony is also performed in the basis of Hindu system. Bengali Brahmin becomes the priests to perform death sacraments. Shradha and Tarpana is also done in the name of dead person in this community. Researcher: A Research Journal of Culture and Society Vol. 3, No. 3, January 2018, Page: 13-32